Using a Student Facilitator in Group Activities of a Large Class Size: An Observational Study - Linh, Duong Que; Huyen, Phan Minh; Hanh, Nguyen Hong; Lan, Do Thi My; Nhung, Duong Thi Cam (Modern Perspectives in Language, Literature and Education Vol. 8, 2021)
In an attempt to create more interesting and motivating lessons for university students, and inspiring learners' autonomy, teachers in the Foreign Language Department of Thai Nguyen University of Economics and Business Administration (TUEBA), Viet Nam have been working intensively to find out the most appropriate methods matched with their teaching context. It has, however, been trouble with all of them because the number of students in each class is up to approximately 60, or more. Hence, it is such a challenge to conduct their lectures effectively because there is a lack of full attention from students in large class size contexts. The answer to this problem should be addressed by using the role of students themselves as facilitators for class activities, which is considered an appropriate solution. This research, thus, was conducted to evaluate the impact of group facilitator strategy in engaging students' English learning in large class sizes. Based on that, several adjustments for another future of this technique are proposed so that learners’ language learning process will be improved.